Efficacy and safety of corticosteroid and immunosuppressive agent combination therapy for pediatric IgA nephropathy: a meta-analysis - Xiong, Xilin (Frontiers in Pediatrics, 2026)
BackgroundIgA nephropathy (IgAN) is a common primary glomerular disease in children. The efficacy and safety of glucocorticoid (GC) and immunosuppressive therapies remain debated. This study aimed to evaluate their clinical effectiveness and safety in pediatric IgAN.MethodsA systematic search was conducted in six databases (PubMed, Web of Science, Cochrane, Embase, CNKI, Wanfang, and VIP), yielding 404 studies, of which eight met inclusion criteria. Eligible studies included RCTs or retrospective studies involving pediatric patients (≤18 years) treated with immunosuppressants plus GC. Outcomes assessed included proteinuria, hematuria, serum creatinine, and adverse events. Two researchers independently extracted and analyzed data. Network meta-analysis (NMA) was performed using R software, incorporating network plots, forest plots, and SUCRA rankings.ResultsNetwork topology showed strong links between GC monotherapy and regimens such as “tacrolimus + GC” and “mycophenolate mofetil (MMF) + GC.” SUCRA rankings indicated superior efficacy of combination therapies in reducing proteinuria and hematuria. Forest plots revealed that all combination regimens significantly reduced proteinuria compared to GC alone (P < 0.05), with only MMF + GC significantly improving hematuria (P < 0.05). No significant differences in adverse event rates were found among treatment groups (P > 0.05). Funnel plots suggested minimal publication bias.ConclusionCombination therapies, especially tacrolimus + GC and MMF + GC, offer greater efficacy than GC monotherapy in pediatric IgAN, without increasing adverse events. These findings support their clinical application, though larger studies are needed to validate results and optimize treatment strategies.